2022
DOI: 10.1007/s40264-022-01260-6
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in Patients with Parkinson’s Disease-Related Psychosis Treated with Pimavanserin Compared with Other Atypical Antipsychotics: A Cohort Study

Abstract: Introduction Pimavanserin is approved in the USA to treat hallucinations and delusions associated with Parkinson's disease psychosis (PDP). Objectives We evaluated mortality in patients with PDP after initiation of pimavanserin or comparator atypical antipsychotics, overall, over time, and across subgroups. Methods A cohort of patients aged ≥65 years in the USA with PDP newly initiating pimavanserin or a comparator atypical antipsychotic (clozapine, quetiapine, risperidone, olanzapine, aripiprazole, brexpipraz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Consideration of pimavanserin for the treatment of PDP should be based on the availability of efficacy data and its unique mechanism of action, which potentially confers a different risk profile than that of antipsychotics 62 which seems to result in decreased mortality risk compared with other atypical antipsychotics. 60 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consideration of pimavanserin for the treatment of PDP should be based on the availability of efficacy data and its unique mechanism of action, which potentially confers a different risk profile than that of antipsychotics 62 which seems to result in decreased mortality risk compared with other atypical antipsychotics. 60 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent cohort study observed lower mortality rates in patients treated with pimavanserin compared with those patients treated with other atypical antipsychotics. 60 …”
Section: Pimavanserinmentioning
confidence: 99%
“… Study Design No. of patients Primary objective Mortality findings Real-world studies of pimavanserin versus other APs Mosholder et al 2022 [47] Retrospective new-user cohort study of patients with PD in Medicare; April 2016 to March 2019 Total: 21,719 All-cause mortality with PIM vs AAPs Mortality HR (95 % CI) for PIM vs AAPs: PIM: 3277 Overall: 0.77 (0.66–0.90) Treated 1–180 days: 0.65 (0.53–0.79) Treated > 180 days: 1.05 (0.82–1.33) AAPs: 18,442 Layton et al 2022 [48] Active comparator, new-user cohort study of patients with PD in Medicare; April 2016 to December 2019 Total: 21,975 All-cause mortality with PIM vs AAPs Mortality HR (95 % CI) for PIM vs AAPs: PIM: 2892 Overall: 0.78 (0.67–0.91) AAPs: 19,083 Alipour-Harris et al 2023 [49] Retrospective study of new users with PD in Medicare; May 2016 to December 2018 Total: 3349 All-cause hospitalization and mortality with PIM vs quetiapine Mortality-adjusted HR (95 % CI) PIM vs quetiapine: PIM: 844 90-day: 0.73 (0.48–1.13); p ≥ 0.05 180-day: 0.80 (0.58–1.10); p ≥ 0.05 1-year: 0.94 (0.74–1.19); p ≥ 0.05 Quetiapine: 2505 Horn et al 2019 [50] Single-center, retrospective cohort study in patients with PDP or DLB Total: 92 Compare time to discontinuation in patients initiating PIM or quetiapine for psychosis Mortality HR (95 % CI) for PIM vs quetiapine: PIM: 45 0.37 (0.06–2.45); p = 0.88 Quetiapine: 47 Nguyen et al 2022 [51] Retrospective new-user cohort study of patients with PD from commercial insurance database; May 2016 to March 2021 …”
Section: Critical Review Of Pimavanserin Mortality Studiesmentioning
confidence: 99%
“…Inverse probability of treatment weighting was used to balance treatment groups, accounting for chronic medical conditions, health care utilization, nursing home residence, medication classes, likelihood of mortality from comorbidities (by Charlson Comorbidity Index score), and frailty score. An analysis by Layton et al also evaluated MR in new users with PDP based on 2016–2019 Medicare claims data (N = 21,975) [48] . Like Mosholder et al, they observed lower MR with pimavanserin versus atypical antipsychotics (HR 0.78; 95 % CI, 0.67–0.91) ( Table 2 ) [48] .…”
Section: Critical Review Of Pimavanserin Mortality Studiesmentioning
confidence: 99%
“…Pimavanserin is a novel antipsychotic that received FDA approval in 2016 to manage psychosis and visual hallucinations in PD Psychosis (Cusick and Gupta, 2023). It has shown to reduce hospitalization and mortality rates compared to quetiapine (Sankary et al, 2020;Layton et al, 2023). Although the average age of the patients in two groups were 80, patients that had claims for hospice or palliative care were excluded from both these studies.…”
Section: Group Amentioning
confidence: 99%